Pengaruh Umur Perusahaan, Profitabilitas dan Pertumbuhan Penjualan Terhadap Tax Avoidance - Tongam Sinambela; Lisa Nuraini (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2021)
This study aims to obtain empirical evidence about the effect of Firm Age, Profitability (Return on Assets), and Sales Growth (Sales Growth) on tax avoidance. This study is a quantitative study using secondary data in the form of financial reports and annual reports of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019. The sample selection used the purpose sampling method. The data analysis technique uses multiple regression analysis with SPSS 20. The results of this study are that the age of the company has a positive and significant effect on tax avoidance. Variable return on assets has a positive effect on tax avoidance. Sales growth variable has no effect on tax avoidance. This is because high sales growth does not necessarily affect the profit generated because each period also produces a different cost of goods sold.